Application Of Medical Play To Reduce The Level Of Hospitalization Anxiety In Preschool Children - Suparno, Suparno; Estiani, Meilina; Aisyah, Aisyah; Saputri, Kurnia (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Anxiety is a response that often appears in children undergoing hospital treatment. The impact of anxiety on children is refusing treatment and slowing recovery. One of the nursing interventions to help reduce anxiety in preschool-aged children is the application of medical play. Medical play is medical play that gives children the opportunity to play and explore medical equipment such as stethoscopes, penlights, thermometers, and others regarding the actions they experience while in the hospital. The aim of the research is to get an overview of the application of medical play to the anxiety response of preschool-aged children who are undergoing hospitalization. The research used the case study method by providing direct application of medical play to respondents which was carried out from February to June 2022 in the Inpatient Room of Dr.Noesmir Baturaja Hospital. Respondents were 2 pre-school children who experienced anxiety due to hospitalization. The results of the study revealed that after nursing interventions in the application of medical play there was a decrease in anxiety levels marked by decreased verbalization of confusion in children, decreased verbalization of worry due to the conditions faced by children, decreased anxiety in children, decreased tension in children, decreased pulse frequency, , and the child does not look pale. Then the pattern of behavior in children improves, marked by the child's concentration improving, the child's sleep patterns improve, and eye contact improves.In conclusion, the application of medical play is an alternative to play therapy that can be used to reduce anxiety levels in pre-school children due to hospitalization